STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN HASIL PENJUALAN DI KAMPUNG KERAMIK DINOYO KOTA MALANG - Maryanto, Tarno; Rakhim Syahida, Amanah (Jurnal Komunikasi Nusantara, 2019)
A good and effective marketing communication strategy is very important to improve the production and sales targets in Kampung Keramik, Kelurahan Dinoyo, Malang. This research examined how marketing communication strategies increase sales and improve good relations with customers and prospective customers. The purpose of this study was to find out and learn marketing communication strategies to maintain good relationships with customers and prospective customers. This study used a descriptive qualitative, with the data collection technique through in-depth interviews, field observations involving informants and documentation as the main data sources. The results of this study indicated that the marketing communication strategy adopted by Kampung Keramik Dinoyo in increasing sales and maintaining relationships with customers and prospective customers was by conducting market selection strategies, product knowledge strategies, distribution strategies and promotion strategies. In conducting promotional activities to increase the sales in Kampung Keramik Dinoyo by putting advertisments in YouTube channel, Instagram, Facebook, online media and websites. Kampung Keramik Dinoyo also conducted a Direct Marketing and Online Marketing Programs that aimed to expand information networks to attract prospective customers and established good relations with their customers.   Keywords: Marketing Communication, Sales, Customers, Dinoyo Ceramics.